Impact of a mechanism-based anti-aggression psychotherapy on behavioral mechanisms of aggression in patients with borderline personality disorder - Honecker, Hannah; Bertsch, Katja; Spieß, Karen; Krauch, Marlene; Kleindienst, Nikolaus; Herpertz, Sabine; Neukel, Corinne (Frontiers in psychiatry, 2021)
Introduction: Aggressive behavior is highly prevalent in patients with borderline personality disorder (BPD) and represents a major burden for patients and their environment. Previous studies have hypothesized threat hypersensitivity, among other mechanisms, as a biobehavioral mechanism underlying aggressive behavior in patients with BPD. The effects of a 6-week mechanism-based anti-aggression psychotherapy (MAAP) for the group setting were tested in comparison to the effects of a non-specific supportive psychotherapy (NSSP) on this hypothesized mechanism and their relation to the effects on aggressive behavior.Methods: To assess mechanisms of reactive aggression, 38 patients with BPD (20 in MAAP and 18 in NSSP) and 24 healthy controls participated in an emotion classification task before and after therapy or at a similar interval of 7 weeks for controls, respectively. In addition, current reactive aggressive behavior was assessed by the externally directed overt aggression score of the Overt Aggression Scale Modified (OAS-M) at both time points. Mixed linear models were used to test for group differences and differential treatment effects.Results: Consistent with previous findings, patients showed longer response latencies and misclassified faces as angry more often than healthy controls. Comparing pre- and post-treatment measurements, the MAAP group showed an increase in response latency in classifying angry faces, whereas the NSSP group showed a decrease in latency. Furthermore, the difference between pre- and post-treatment response latencies in classifying emotional faces correlated with the reductions in reactive aggression in the MAAP group, but not in the NSSP group or healthy controls.Conclusion: The results suggest an impact of MAAP on threat sensitivity as well as cognitive control, which has also been previously hypothesized as a biobehavioral mechanism underlying reactive aggression in patients with BPD. In addition, our findings shed light on the importance of these two biobehavioral mechanisms underlying reactive aggression as mechanisms of change addressed by MAAP. Further studies are needed to determine whether the behavioral change is stable over time and to what extent this change is related to a stable reduction in reactive aggression in a larger group of patients with BPD.